PENGETAHUAN, SIKAP DAN PERILAKU KEPALA RUMAH TANGGA TERHADAP PENGELOLAAN AIR LIMBAH RUMAH TANGGA (KASUS DI KELURAHAN PEKAPURAN RAYA ) KECAMATAN BANJARMASIN TIMUR KOTA BANJARMASIN - Wahyu Hardi Cahyono; Wahyu Wahyu; Siti Aisyah; Bunda Halang (Universitas Lambung Mangkurat, 2011)
One of the efforts of Banjarmasin City Government to reduce water pollution by establishing Local Company Waste Water Management, which the company functions to process and dispose of household wastewater population by installing waste water pipe network to the home population ( off site system), but still many heads of households do not take advantage of the IPAL. Based on the results of research in Kelurahan Pekapuran Raya found that public knowledge about domestic waste water are still many who do not know the household waste water. The attitude of rejection of the existence of IPAL with a variety of reasons they put forward like objection to the demolition of the road in its territory, the objections of the payment of 25% of PDAM tariffs and went along with refuse because there are influential figures in society also does not come IPAL utilize the existence of the advice given is Government should further enhance efforts to disseminate information about the management of domestic wastewater through socialization to community leaders and through media information or conduct training to the village which will be forwarded to the local community. Development of pilot areas that will both domestic waste water management, will provide definitive proof to the people who have or are still opposed to the program management of household waste water.